Обозначим проще - a и b.
ДАНО
a = 3 - 3i
b = 1 + i
Сумма
a+ b = 3 - 3i + 1 + i = 4 - 2i
Разность
a - b = 3 - 3i - 1 - i = 2 - 4i
Произведение - помним, что = i*i = -1.
a*b = (3-3i)(1+i) = 3 + 3i - 3i -3(i*i) = 3+3 = 6
Частное - умножаем на (1 - i) чтобы избавиться в знаменателе
2.8x-3.6=3.7x
2.8x-3.7x=3.6
-0.9x=3.6
-x=4
x=-4
356×34=12.104 3,56×3,4=12.104 2)1073×81=86.913 1,073×8,1=8.6913 3)74×625=46.250 0,074×6,25=0,4625
1) 36*8=288
2)288/6 = 48
3) 48-36 = 12 (новых)
4. 36 - 100%
48 - х
х = 48*100/36 = 133%
133-100 = 33 (на 33 %)